REKONSTRUKSI SISTEM PERADILAN PIDANA INDONESIA - Mardjono Reksodiputro (Jurnal LEX SPECIALIS, 2010)
It was so right if the criminal law in Indonesia is also called the legacy of colonial goverment of Netherland, because the frame of  the system of our criminal law is recently used by them during the colonial time, that system it can still be used until now because it capablility is include in every aspect of our philoshophi and culture, althoght some perfection is still needed in some aspect it doesnt meant law enforment it cannot acommplished, because to keep maintain stablity the due process of lawit must be established, we must avoid every act that will be dishonor the law, becuse of that reconstruction of criminal law system is still needed in Republic of Indonesia. Key Note : Reconstruction of criminal law system